Indigenous Yakut male athletes: sports-specific constitutions and somatic types - Vinokurova, S. P.; Senizova, M. I.; Gulyaeva, S. S.; Abramova, V. R. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to rate and analyze the sports-specific body constitutions and types in the indigenous Yakut male athletic groups.